2020
DOI: 10.1002/ccd.29261
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in U.S. hospitalizations for chronic limb‐threatening ischemia

Abstract: Background: Seasonal variation in coronary artery disease is well described, with a peak in the winter and a trough in the summer. However, little is known about seasonal trends in hospital admission for critical limb-threatening ischemia (CLTI) and associated outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…31 While the high mortality rate combined with a low number of less severe cases raises questions concerning attribution, more importantly, studies on patients with severe cardiovascular conditions show that influenza vaccination can significantly improve their prognosis 32,33 Studies on multiple unrelated conditions have demonstrated a similar pattern, with barely noticeable seasonal variability in amputation rates for critical limb-threatening ischemia, but hospitalization patterns aligning with influenza waves. 34 An elevated incidence of hospitalization for acute kidney injury was observed in winter, and during this period, the mortality rate among those hospitalized was found to be highest. 35 An increased winter mortality rate was observed in intensive care units, which remained statistically significant even after adjusting for diagnosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…31 While the high mortality rate combined with a low number of less severe cases raises questions concerning attribution, more importantly, studies on patients with severe cardiovascular conditions show that influenza vaccination can significantly improve their prognosis 32,33 Studies on multiple unrelated conditions have demonstrated a similar pattern, with barely noticeable seasonal variability in amputation rates for critical limb-threatening ischemia, but hospitalization patterns aligning with influenza waves. 34 An elevated incidence of hospitalization for acute kidney injury was observed in winter, and during this period, the mortality rate among those hospitalized was found to be highest. 35 An increased winter mortality rate was observed in intensive care units, which remained statistically significant even after adjusting for diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…Studies on multiple unrelated conditions have demonstrated a similar pattern, with barely noticeable seasonal variability in amputation rates for critical limb‐threatening ischemia, but hospitalization patterns aligning with influenza waves. 34 An elevated incidence of hospitalization for acute kidney injury was observed in winter, and during this period, the mortality rate among those hospitalized was found to be highest. 35 An increased winter mortality rate was observed in intensive care units, which remained statistically significant even after adjusting for diagnosis.…”
Section: Discussionmentioning
confidence: 98%